THE STUDY OF TRANSIENT PROCESSES OF THE FREQUENCY-REGULATED SYNCHRONOUS ELECTRIC DRIVE - B. I. Firago; S. V. Aleksandrovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In order to improve the power indices and to simplify the system of frequency speed control the scope of application of synchronous variable-frequency electric drives with independent frequency setting is being expanded. The synchronous motors with electromagnetic excitation and permanent magnet excitation in various industrial settings, including load-lifting machines and mechanisms, are used. As compared with the asynchronous frequency-regulated electric drives the synchronous ones have lower power loss, harder mechanical characteristic without feedback for speed and the simplest law of frequency control, i. e., a proportional one that, however, provides the maximum electromagnetic torque of the motor constant at all frequencies, due to the constant magnetic flux. The article concerns an analytical study of transient processes of synchronous electric drive with consideration of the influence of damping winding when the motor supply voltage frequency varies linearly during the transient time. As a result of the analysis the formulas have been obtained that make it possible to calculate the angular velocity of the rotor and the electromagnetic torque of the motor at start-up, braking, and impingement and discharge of loads, evaluating the quality of the transition process and tracking the maximum value of the electromagnetic torque, that must not exceed the permissible value. Validation of the developed technique of calculation of transient processes of synchronous electric drive has been obtained by comparison of calculations according to the formulas with the simulation results of the electric drive on the basis of the synchronous motor of the SD3 13-34-6 type (power of 500 kW and voltage of 6 kV).